Integrasi Akad Pembiayaan dan Akad Rahn: Analisis Kritis terhadap Implementasi Fatwa DSN No. 92 Tahun 2014 pada PT. Pengadaian, Jakarta - Yupiter, Yupiter; Huda, Nurul; Tanjung, Hendri (AL-FALAH : Journal of Islamic Economics, 2019)
Purpose: The purpose of this article is to critically examine how the implementation of the MUI DSN Fatwa No. 92 of 2014 concerning financing accompanied bycontract rahn at PT. Procurement, Jakarta. Design/Method/Approach : A qualitative approach is applied in this study, with design an exploratory research. The analysis unit is PT. Procurement, Jakarta. While the library research, and interviews are used as the main instruments in collecting relevant data.Findings: In general, this study succeeded in identifying several important things, namely: First, that between DSN No. 92 of 2014 with the practices applied by PT. Procurement, Jakarta, is appropriate. Secondly, Islamic Pawnshop is relatively new as a financial system. This is one of the obstacles for PT. Procurement, Jakarta, in operating Islamic products.Originality/Value: This research is believed to be important and significant in contributing to the theory. Especially, in terms of filling in the blanks of examplars of theories about the conformity of the DSN Fatwa No. 92 of 2014 with practice, especially at PT. Procurement, Jakarta.